Possibilities and Challenges of Dragon Fruit in Chapainawabganj Region of Bangladesh from the Growers Perspective - Mithun Kumar Ghosh; Mst. Lamia Jahan; Fabia Farjana; Md. Zahid Hasan; Kazi An Nahian (Turkish Journal of Agriculture: Food Science and Technology, 2023)
Farmers in Bangladesh are enthusiastic in dragon fruit farming as a new and promising crop that offers both difficulties and potential. The purpose of the study was to examine the advantages and disadvantages of this novel fruit from the perspective of growers. It is a descriptive survey research which was conducted in purposively selected four Upazilas of Chapainawabganj region of Bangladesh including Chapainawabganj Sadar, Gomastapur, Nachol, and Godagari from 16th April to 25th May, 2022. Pearson’s correlation test was administered to determine the relationship between socio-demographic characteristics of the growers and their knowledge on dragon fruit production. Socio-demographic profile of the randomly selected growers of the study revealed that majority of the respondents were in their middle age, highly educated, had a medium annual income with medium sized land, little farming experience, less training and higher cosmopolitan behavior. Majority of the dragon fruit growers showed high level of understanding regarding dragon fruit cultivation and their fellow farmers and mass media were determined to be the most effective sources of information. According to the study’s findings, the majority of farmers were inspired to grow dragon fruit because it is more resistant to pests and diseases, promotes excellent health, yields for a long time, and can be grown from both seeds and cuttings. Furthermore, the fruit has a higher profit margin than other field crops. Weeds, bird invasions, high labor expenses, lack of technical knowledge of farmers on dragon fruit farming were recognized as major obstacles to fruit production. According to a correlation analysis, farmers’ age, extension contacts, and cosmopolitan nature were significantly and positively correlated with their knowledge of growing dragon fruit. More government support, especially from the Department of Agricultural Extension (DAE), and fixing the issues described above could increase the fruit’s future prospects in the country.